Discovering biblical equality biblical, theological, cultural & practical perspectives - Pierce, Ronald W. 1946-; Westfall, Cynthia Long 1953-; McKirland, Christa L. 1985- (InterVarsity Press, 2021)
"The conversation about gender roles in Christian life and the church has evolved, but the topic continues to inspire debate and disagreement. Now in its third edition, this fresh, positive defense of gender equality brings together scholars firmly committed to the authority of Scripture to explore historical, biblical, theological, cultural, and practical aspects of this discussion"--
Keywords: Bibel; Geschlechterverhältnis; Gleichberechtigung; Sex role / Biblical teaching; Equality / Biblical teaching; Evangelicalism; Aufsatzsammlung